Enhancing internship students’ performance through structured training and development programs - Ni Luh Putu Inten Rumini; Sagung Mas Suryaniadi; Ni Ketut Lasmini; Ni Wayan Sumetri (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study examines how structured training and development initiatives improve the performance of internship students by strengthening both hard and soft skills. Internships are widely recognized as a bridge between academic learning and workplace demands, contributing to technical competence, employability, and professional growth. The research aims to (1) assess the impact of pre internship and on the job training on interns’ task performance, and (2) analyse how soft skills (communication, teamwork, problem solving) and hard skills jointly predict internship outcomes. A mixed methods design is proposed, combining surveys of interns and supervisors with semi structured interviews to capture perceived changes in competence, confidence, and work readiness. Quantitative data will be analysed using regression and mediation models to test the contribution of training intensity and learning climate to performance, while qualitative data will be thematically analysed to explore mechanisms such as mentoring quality and feedback practices. The study concludes that well designed training and development, supported by clear objectives and effective supervision, significantly enhance internship performance and facilitate smoother school to work transitions.